The interaction between a driver and intelligent transport systems - Alica Kalašová; Kristián Čulík; Simona Skřivánek-Kubíková (Acta Polytechnica CTU Proceedings, 2022)
A road traffic system is a complex system which includes four main parts – human, vehicle, road, and the natural environment. Road safety in Slovakia is based on the strategy of the government, as well as on European policies. It is important to implement complex strategic measures in the fields of traffic accidents, emergency services, and definitions of classifying injuries and deaths to decrease the number of injuries. The National plan’s measures must be included in strategic documents, which discuss road safety. It is necessary to combine several strategic goals in the transport process, to provide transport services according to users’ needs. The increase in the safety on the roads is a process that tries to mitigate negative impacts of traffic accidents. In recent years, Intelligent Transport Systems (ITS) have reduced several road traffic fatalities, particularly amongst passenger deaths. Various types of intelligent transport systems (ITS) are currently implemented in passenger cars and provide a higher level of road safety. However, there is a need to assess the effects of these systems on traffic safety. Drivers must perceive technologies as useful, effective, easy to use, affordable, and socially acceptable. There is also a need for drivers’ willingness to use ITS. This paper discusses the benefits of using intelligent transport systems (ITS) in urban conditions. They can enable the safety of road traffic. We verified it with a questionnaire. We have gathered 519 answers. The results were processed and evaluated in this article.